PENTINGNYA ASURANSI PEMBIAYAAN DAN PENJAMINAN SIMPANAN NASABAH BANK SYARIAH MELALUI LEMBAGA PENJAMIN SIMPANAN (LPS) - Nila Khoirun Na’ili; Diva Wahyu Tias Saputri; Kharismatul Ulfiah; Binti Nur Asiyah (Cahaya Ilmu Bangsa, 2024)
Islamic banks are now continuing to experience development, both in terms of assets, office network and legal recognition. This requires supporting arrangements in the sharia banking sector through financing insurance and guaranteeing customer deposits through LPS. In sharia banks, financing insurance is very important in maintaining financial stability from unexpected financial risks. Guaranteeing sharia bank customer deposits guaranteed by LPS, such as current accounts and savings, is based on the wadiah principle. This guarantee can increase customer confidence. The research uses a qualitative approach with literature studies, collecting secondary data from various official sources related to LPS and insurance. This approach aims to thoroughly understand the importance of financing insurance and guaranteeing customer deposits in Islamic banks through LPS. The research results show that the implementation of financing insurance and deposit guarantee policies by LPS reduces financial risk and maintains public trust, as well as supporting the stability of the national financial system.